CHARLILI (MENCHARGE LILIN LITERASI) SAAT PANDEMI BERBUAH BUKU ANTOLOGI - Wahyuni Budi Hastuti Sumarno (Balai Diklat Keagamaan Jakarta, 2022)
Abstract This study aims to describe literacy development strategies through writing culture to produce an anthology of short stories. The movement to write books with students is an effort to motivate students to write about their learning experiences during the pandemic. With the activity of writing books for students at MTs Negeri 34 Jakarta, it is hoped that it can increase the literacy movement of madrasa residents. The methodology used in this paper is descriptive qualitative by describing the mentoring activities in the project of making an anthology book. The activity of writing an anthology book with students is carried out in several stages, namely (1) the implementation stage in the form of providing understanding, motivation; (2) the implementation stage, students join the WhatsApp group, providing signs for writing distance learning experiences; (3) the completion stage in the form of activities sending manuscripts, editing manuscripts by each student, sending manuscripts to publishers, editing manuscripts sent from publishers, printing processes, promotions and responses from students after receiving their books. Writing books can give students flexibility in exploring their experiences, developing vocabulary, providing strengthening character education. So that the final result to be achieved is a project-based learning product, namely an anthology of short stories with an ISBN. Abstrak Penelitian ini bertujuan untuk menggambarkan stategi pengembangan literasi melalui budaya menulis untuk menghasilkan buku antologi cerpen. Gerakan menulis buku bersama siswa ini sebagai upaya untuk memotivasi siswa untuk menulis tentang pengalaman belajar selama pandemi. Dengan adanya kegiatan menulis buku, siswa di MTs Negeri 34 Jakarta diharapkan dapat meningkatkan gerakan literasi warga madrasah. Metodologi yang digunakan pada penulisan ini adalah deskriptif kualitatif dengan menggambarkan kegiatan pendampingan pada proyek membuat buku antologi. Kegiatan menulis buku antologi bersama siswa dilakukan melalui beberapa tahap, yaitu: (1) tahap pelaksanaan berupa kegiatan pemberian pemahaman, motivasi; (2) tahap pelaksanaan, siswa bergabung dalam grup WhatsApp, pemberian rambu-rambu penulisan pengalaman pembelajaran jarak jauh; (3) tahap penyelesaian berupa kegiatan pengiriman naskah, edit naskah oleh masing-masing siswa, pengiriman naskah ke penerbit, edit naskah yang dikirim dari penerbit, proses cetak, promosi dan tanggapan dari siswa setelah menerima buku hasil karya mereka. Menulis buku dapat memberikan keleluasan siswa dalam mengeksplor pengalamannya, mengembangkan perbendaraan kata, memberikan penguatan pendidikan karakter. Sehingga hasil akhir yang dicapai adalah sebuah produk pembelajaran berbasis proyek yaitu sebuat buku antologi cerpen ber-ISBN.